2017
DOI: 10.1038/srep44564
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel chemotherapeutic strategies for metastatic uveal melanoma

Abstract: Melanoma of the uveal tract accounts for approximately 5% of all melanomas and represents the most common primary intraocular malignancy. Despite improvements in diagnosis and more effective local therapies for primary cancer, the rate of metastatic death has not changed in the past forty years. In the present study, we made use of bioinformatics to analyze the data obtained from three public available microarray datasets on uveal melanoma in an attempt to identify novel putative chemotherapeutic options for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 41 publications
1
51
0
1
Order By: Relevance
“…In addition, we also evaluated the transcriptomic analysis of MIF, DDT and their receptors in the brains of a mouse model of alcoholism. This analysis was carried out by DNA microarray analysis that represents a useful in silico toll for the better understanding of pathogenic pathways and the possible prediction of new diagnostic therapeutic approaches in several clinical settings, including immunoinflammatory and autoimmune diseases and fibrotic diseases (45,46,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Our analysis first demonstrated that no differences in the expression of MIF, DDT and their receptors can be found in brains of both rodent models of AUD and patients with this condition.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, we also evaluated the transcriptomic analysis of MIF, DDT and their receptors in the brains of a mouse model of alcoholism. This analysis was carried out by DNA microarray analysis that represents a useful in silico toll for the better understanding of pathogenic pathways and the possible prediction of new diagnostic therapeutic approaches in several clinical settings, including immunoinflammatory and autoimmune diseases and fibrotic diseases (45,46,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Our analysis first demonstrated that no differences in the expression of MIF, DDT and their receptors can be found in brains of both rodent models of AUD and patients with this condition.…”
Section: Discussionmentioning
confidence: 83%
“…pathways and therapeutic targets in several diseases, including cancer and autoimmune, fibrotic, neurodegenerative and infectious diseases (22,23,(54)(55)(56)(57)(58)(59). Presti et al (22) utilized RNA-seq data of 281 and 283 DNA-sequenced glioblastoma multiforme and low-grade glioma patients, respectively, to evaluate the expression levels of migration inhibitory factor (MIF) and related genes in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we first analyzed the expression levels of IL37, SIGIRR, and IL18R1 in circulating immune cells from MS patients. In particular, we performed a DNA microarray analysis that represents a useful in silico tool for the better understanding of pathogenic pathways and the possible prediction of novel diagnostic therapeutic strategies, as it has been shown in a variety of clinical settings, such as autoimmune and immunoinflammatory diseases [38][39][40][41][42][43][44] and cancer [45][46][47][48][49][50][51], leading to the identification of novel therapeutic targets [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%